Analisis E-Service Quality Terhadap Kepuasan Konsumen Pada I Am Geprek Bensu - Triana, Jessica; Rosa, Aslamia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to analyze the effect of e-service quality in customer satisfaction at I Am Geprek Bensu Palembang through the ShopeeFood channel at least 1 time in the last 4 months (January-April 2023) partially and simultaneously, and to determine the e-service quality variable that has a dominant influence on customer satisfaction at I Am Geprek Bensu Palembang. The sampling technique used in this research Is non-probability sampling with purposive sampling method and using multiple linear regression analysis with the help of SPSS 23 software. The method used for data collection, namely questionnaires with a Likert scale totaling 140 respondents. The results of this study indicate that the partial test (t test) of e-service quality variables in the dimensions of efficiency (X1), fulfillment (X2), privacy (X4), responsiveness (X5), compensation (X6) has a positive and significant effect on customer satisfaction. The simultaneous test (F test) proves that the dimensions of efficiency (X1), fulfillment (X2), system availability (X3), privacy (X4), responsiveness (X5), compensation (X6), and contact (X7) have an effect on the dependent variable, namely customer satisfaction (Y). Keywords: E-Service Quality, Customer Satisfaction, Efficiency, Fulfillment, System Availability, Privacy, Responsiveness, Compensation, Contact